2016
DOI: 10.12775/equil.2016.001
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic forecast uncertainty in the euro area

Abstract: This paper estimates aggregate measures of macroeconomic uncertainty from individual density forecasts by professional forecasters. The methodology used in the paper improves on the existing literature along two dimensions. Firstly, it controls for changes to the composition of the panel of respondents to the survey. And secondly, it assigns more weight to the information submitted by forecasters with better forecasting performance. Using data from the European Central Bank’s Survey of Professional Forecasters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…3 Despite the growing interest in the SPF, there is a surprisingly scarce amount of research on the factors that affect non-response to this survey. Engelberg et al (2011) and López-Pérez (2016) explored the effects of changes in the composition of the panel of participants on aggregate results from the survey, but the decision to reply is not investigated. Furthermore, Engelberg et al (2011Engelberg et al ( : 1076 concluded that,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Despite the growing interest in the SPF, there is a surprisingly scarce amount of research on the factors that affect non-response to this survey. Engelberg et al (2011) and López-Pérez (2016) explored the effects of changes in the composition of the panel of participants on aggregate results from the survey, but the decision to reply is not investigated. Furthermore, Engelberg et al (2011Engelberg et al ( : 1076 concluded that,…”
Section: Introductionmentioning
confidence: 99%
“…If increases in uncertainty augment the cost of forecasting, the removal of these observations would bias the results presented in this paper against any negative effect of uncertainty on response. 13 The interested reader may find in López-Pérez (2016) all the details about the preliminary treatment of the data.…”
mentioning
confidence: 99%
“…4 Despite the growing interest in the SPF, there is a surprisingly scarce amount of research on the factors that affect non-response to this survey. Engelberg et al (2011) and López-Pérez (2016) explored the effects of changes in the composition of the panel of participants on aggregate results from the survey, but the decision to reply is not investigated. Furthermore, Engelberg et al (2011Engelberg et al ( : 1076 concluded that, "We observed in the Introduction that, in the absence of knowledge of the forecaster recruitment and participation process, the assumption that data are missing completely at random is not refutable.…”
Section: Introductionmentioning
confidence: 99%
“…Turning now to the measure of uncertainty, the data is obtained from López-Pérez (2016) where several measures of individual uncertainty are computed from SPF density forecasts. One of these measures, the Gini index of the individual density forecast, is used in this paper.…”
mentioning
confidence: 99%
See 1 more Smart Citation